2018
DOI: 10.1093/pubmed/fdy214
|View full text |Cite
|
Sign up to set email alerts
|

The elephant in the room? Why spatial stigma does not receive the public health attention it deserves

Abstract: The elephant in the room? Why spatial stigma doesn't receive the public health attention it deserves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 40 publications
1
32
0
Order By: Relevance
“…A further theme was the perceived stigmatisation of areas labelled as 'bad'. This supports the argument that spatial stigma is an under-researched issue which may have wider equity impacts [51]. Conversely, the case study findings revealed community strengths and capacities which could be drawn on in responding to local priorities ( Table 1).…”
Section: Discussionsupporting
confidence: 73%
“…A further theme was the perceived stigmatisation of areas labelled as 'bad'. This supports the argument that spatial stigma is an under-researched issue which may have wider equity impacts [51]. Conversely, the case study findings revealed community strengths and capacities which could be drawn on in responding to local priorities ( Table 1).…”
Section: Discussionsupporting
confidence: 73%
“…25 Stigma is a fundamental cause of health inequalities, 26 and international evidence has demonstrated that poverty stigma is associated with poor mental health among low-income groups. 27 Individuals living in socioeconomically deprived areas may also experience 'spatial' stigma, which similarly has a range of adverse health effects for residents 28 and, crucially, may be unintentionally exacerbated by media and public health professionals' reports of regional health inequalities. 29 Given the continued focus on Glasgow's relatively poor health it is possible that the city is more vulnerable to such stigmatising processes.…”
Section: Excess Mortality and Mental Health In Glasgowmentioning
confidence: 99%
“…The participants connected these inequalities and the reputation of the area to their own health and well-being, including stress and anxiety. Keene and Padilla (2014) have recognised this mechanism acknowledging that “disadvantaged places contribute to multiple physical and mental health outcomes” (p. 392), whilst Halliday et al (2020) have called for greater public health attention to spatial stigmas as a public health concern. Our paper demonstrates that children and young people can feel this stigma, and the socio-spatial polarisation that results may impact negatively on their health and well-being.…”
Section: Discussionmentioning
confidence: 99%